OZONIOTHERAPY AS PAIN TREATMENT IN LOWER LIMBS: SYSTEMATIC REVIEW - Vieira Nascimento Priesnitz, Aline (Health and Society, 2024)
To evaluate through a systematic review the effectiveness of ozone therapy for the treatment of pain in the lower limbs. Methods: To achieve this objective, the methodology adopted involved a systematic search in the ScienceDirect, PubMed and SciELO databases, using a structured combination of specific keywords. Literature review studies and clinical studies relevant to the theme were included. The inclusion criteria involved the selection of studies in English, Portuguese and Spanish that addressed the application of ozone therapy in the treatment of pain in the lower limbs. We excluded articles that had no direct relationship with the theme, as well as case reports, case series, coursework, theses and dissertations. Conclusion: Chronic pain in the lower limbs is a prevalent condition, often caused by traumatic injuries, degenerative joint diseases, peripheral neuropathies and/or circulatory disorders. In addition to the physical impact, this condition limits mobility and significantly affects people’s quality of life. Conventional treatments, although widely used, often have limited efficacy and potential adverse side effects, driving the search for more effective and safe therapeutic alternatives. Utilizing the oxidative potential of ozone, this therapy is administered in various forms, including topical, subcutaneous, venous and rectal applications.